FSI-simulation of ductile fracture propagation and arrest in pipelines: Comparison with existing data of full-scale burst tests. (May 2020) - Keim, V.; Paredes, M.; Nonn, A.; Münstermann, S.
Abstract: The fracture propagation and arrest control for pipelines transporting rich natural gases and high vapor pressure liquids is based on the Battelle Two-Curve Model (BTCM). Distinct limitations of this model were demonstrated for past and modern steels and gas mixtures. These can be related to the insufficient description of individual physical processes and interactions between the pipe material and transported mixture during the running ductile fracture. In the past, fluid-structure interaction (FSI) models enabled a more sophisticated, coupled analysis of the failure scenario. To quantify their capability of describing the multi-physical processes, the FSI models need to be verified by experimental data from full-scale burst tests (FSBT). Therefore, this paper deals with the simulation of five FSBTs from the literature on API grade X65 pipes with different pipe geometries, mixtures and initial conditions. The FSI is modeled by the coupled Euler-Lagrange (CEL) method. The modified Mohr-Coulomb (MMC) model is implemented in the CEL framework to describe the deformation and ductile fracture in the X65/L450 pipes. 3D Euler equations are used to calculate the mixture decompression with the GERG-2008 equation of state defining the volumetric behavior of a CO2 -rich mixture, CH4 and H2 . The extended model considers the effect of soil backfill on the pipe deformation and inertia. The numerical predictions agree well with the experimental findings in terms of the crack propagation speed and arrest length underlining the capability of the developed numerical tool. Highlights: Deformation and ductile fracture of X65-UOE-pipes are described by the modified Mohr-Coulomb (MMC) model considering plastic anisotropy, strain rate and temperature effects as well as the isotropic ductile fracture as a function of the underlying stress conditions. A two-step recalibration procedure based on experimental data from Battelle Drop-Weight Tear (BDWT) tests is proposed to enable the application of material model parameter sets for different toughness levels. The mixture decompression of methane, hydrogen and CO2-rich mixtures is described by the GERG-2008 equation of state in a 3D-Euler fluid model. The extended model considers the effects of partial and complete soil backfill with the Mohr-Coulomb (MC) model defining the mechanical response of the soil material. The predictions agree well with experimental findings and underline the capability of the developed methodology.